Rudimentos, y algo más, de gramática histórica española. Diez ejemplos bienhallados, precedidos de un entorno particularmente expresivo (1901-1967) - Polo, José (Revista de Filología Románica, 2006)
One book on History of the Spanish Language and nine on Historical Grammars (all four, from twenty century, and elementary ones) are presented: Barberena, Rufo Mendizábal, González Moreno, Eusebio Hernández, Díez Mateo, J. N. Hidalgo, Agustín Mateos...